İLK DÖNEM ENDÜLÜS DENİZCİLİĞİ VE ENDÜLÜS DONANMASININ TEŞEKKÜLÜ. - CURUK, Osman (Dinbilimleri Journal, 2025)
This article examines early Andalusian seafaring and the establishment process of the Andalusian navy. In Andalusia, the establishment of an official navy was delayed due to political instability and internal conflicts following the Muslim conquest. The Viking attack in 844 revealed the need for a strong naval power in Andalusia, which paved the way for the establishment of the navy during the reign of Abd al-Rahman II. The article emphasizes that the activities of the seafarers were generally characterized as piracy, but these actions were actually organized military expeditions. It also notes that the seafarers in Andalusia contributed to official maritime activities by coming under state control.